Multiple short intervals induce longer time above 90% of maximal oxygen consumption than long intervals when matched by similar fixed intensity, but not during self-paced cycling ergometry - Appelhans, D.; Rønnestad, B.; Skovereng, K. (International Journal of Sports Physiology and Performance, 2025)
In previous studies comparing different interval protocols for high-intensity interval training, large differences in time above 90% of maximal oxygen consumption (VO2max) have been observed. Differences can possibly be attributed to session design or intensity control. Twelve well-trained cyclists and triathletes (VO2max: 68 [6.3] mL·min-1·kg-1) performed 2 different cycling ergometry interval protocols of 3 × 13 × 30/15 seconds (short interval [SI]) and 6 × 5 minutes (long interval [LI]), each with a fixed intensity based on percentages of maximal aerobic power and self-paced approach with maximal effort. The time above 90% VO2max was significantly greater for SI than LI in fixed (P < .01) but not in self-paced intensity (P = .321). All physiological parameters assessed and power outputs were higher in self-paced than fixed (all P < .001; all n2p>.795), resulting in an increased time above 90% VO2max for SI (1130 [204] vs 420 [259] s) and LI (1016 [312] vs 178 [159] s). When the short recovery periods are included in total interval work duration in SI, and SI and LI are matched on duration and fixed intensities (similar percentage of maximal aerobic power), SI gave greater time above 90% VO2max. However, when SI and LI were performed with the self-paced approach and maximal effort, the exercise intensity became higher and there were no differences in time above 90% VO2max.